2020
DOI: 10.1590/0034-7167-2019-0700
|View full text |Cite
|
Sign up to set email alerts
|

Mock panels as an active teaching methodology in the education of nursing doctors

Abstract: Objective: To analyze the experience of doctorate students in the use of mock panels as an active methodology of teaching in Nursing post-graduation. Method: Experience report on the use of mock panels in the discipline Advanced Methods for Researches in Health and Nursing II, offered in the doctorate course of the Nursing Post-graduate Program from the Universidade Federal do Rio Grande do Norte. Results: The mock panels contributed for the doctorate of nurses and enabled students to take on the role of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
(13 reference statements)
0
2
0
2
Order By: Relevance
“…Lastly, as much time and effort are required to design a typical original mock trial, a creative method should be sought to modify the mock trial design for effective operation within a limited educational period. Previous studies showed creative applications of the mock trial method of EBP education, where a selected set of students as the mock panel held discussions in a PhD course [ 27 ] or a PhD student made a presentation in an undergraduate class [ 28 ]. In addition, since running a mock trial as regular coursework would place a high burden on the educator, a method should be developed to encourage student participation in mock trials run at hospitals [ 25 ] or to provide it as part of a non-regular course, such as a mock trial club activity.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, as much time and effort are required to design a typical original mock trial, a creative method should be sought to modify the mock trial design for effective operation within a limited educational period. Previous studies showed creative applications of the mock trial method of EBP education, where a selected set of students as the mock panel held discussions in a PhD course [ 27 ] or a PhD student made a presentation in an undergraduate class [ 28 ]. In addition, since running a mock trial as regular coursework would place a high burden on the educator, a method should be developed to encourage student participation in mock trials run at hospitals [ 25 ] or to provide it as part of a non-regular course, such as a mock trial club activity.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of practical teaching, simulation stands out among the most used strategies, which, by allowing a closer approach to professional practice, leads to the development of "clinical reasoning, communication, self-confidence, autonomy, critical and reflective learning, creativity, interdisciplinary training and articulation of cognitive, psychomotor and affective attributes" Ghezzi et al, 2021, p.7) of the student and is still associated with efficacy and better clinical results (Silva & Oliveira-Kumakura, 2018;Morais et al, 2020;Ghezzi et al, 2020;Ghezzi et al al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…As MAA estão alicerçadas em um princípio teórico significativo que é o desenvolvimento da autonomia do discente. Isso indica que a educação contemporânea deve pressupor um estudante capaz de autogerenciar seu processo de formação (MORAIS et al, 2020).…”
Section: Inserção Das Metodologias Ativas De Ensino-aprendizagem (Maa...unclassified